Wireless coordinated multicell systems : architectures and precoding designs - Nguyen, Duy H. N. (SpringerBriefs in Computer Science, 2014)
This SpringerBrief discusses the current research on coordinated multipoint transmission/reception (CoMP) in wireless multi-cell systems. This book analyzes the structure of the CoMP precoders and the message exchange mechanism in the CoMP system in order to reveal the advantage of CoMP. Topics include interference management in wireless cellular networks, joint signal processing, interference coordination, uplink and downlink precoding and system models. After an exploration of the motivations and concepts of CoMP, the authors present the architectures of a CoMP system. Practical implementation and operational challenges of CoMP are discussed in detail. Also included is a review of CoMP architectures and deployment scenarios in the LTE-Advanced standard. Readers are exposed to the latest multiuser precoding designs for the CoMP system under two operating modes, interference aware and interference coordination. Wireless Coordinated Multi cell Systems: Architectures and Precoding Designs is a concise and approachable tool for researchers, professionals and advanced-level students interested in wireless communications and networks.